(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
Quality by Design, Dr. Joseph M. Juran first introduced this concept in the 1970s., represents a risk-based approach to drug development, emphasizing continuous risk management throughout a product's lifecycle and predefined objectives. Implementation guidelines are detailed in the International Council of Harmonization (ICH) standards Q8–11. About a decade ago, the European Medicines Agency (EMA) adopted QbD principles for the pharmaceutical regulatory framework in the European Union. Despite recognition as essential in 2014, the integration of QbD into European marketing authorization applications remains limited and is not standardized. Using information from EPARs, a recent four-year study (2020–2023) aimed to evaluate how QbD principles were applied in all EU-approved marketing applications. Approximately 33.13% (111) out of 335 pharmaceuticals were developed using quality by design (QbD) principles, and 37.01% of all permitted drugs (77 out of 208 under article 8(3)) used QbD. Remarkably, over the course of four years, 30–40% of approved items that were presented as stand-alone documents adopted QbD. Most approved fixed-dose combination medications (71% in 2020 and 100% from 2021 to 2023) were, interestingly, developed utilizing a QbD strategy. Furthermore, four applications for market authorization incorporating QbD principles in the dossier were denied by the EMA. In conclusion, according to EPARs, regulatory dossiers lack complete QbD implementation, but the modest use of QbD components suggests a growing interest among businesses, potentially indicating a shift towards accepted development standards. Effective communication between regulatory bodies and companies is crucial for addressing challenges in QbD application.